The Spatiotemporal Variations of Runoff in the Yangtze River Basin under Climate Change - Ziwei Xiao; Peng Shi; Peng Jiang; Jianwei Hu; Simin Qu; Xingyu Chen; Yingbing Chen; Yunqiu Dai; Jianjin Wang (Advances in Meteorology)
A better understanding of the runoff variations contributes to a better utilization of water resources and water conservancy planning. In this paper, we analyzed the runoff changes in the Yangtze River Basin (YRB) including the spatiotemporal characteristics of intra-annual variation, the trend, the mutation point, and the period of annual runoff using various statistical methods. We also investigated how changes in the precipitation and temperature could impact on runoff. We found that the intra-annual runoff shows a decreasing trend from 1954 to 2008 and from upper stream to lower stream. On the annual runoff sequence, the upstream runoff has a high consistency and shows an increasing diversity from upper stream to lower stream. The mutation points of the annual runoff in the YRB are years 1961 and 2004. Annual runoff presents multitime scales for dry and abundance changes. Hurst values show that the runoffs at the main control stations all have Hurst phenomenon (the persistence of annual runoff). The sensitivity analyses of runoff variation to precipitation and temperature were also conducted. Our results show that the response of runoff to precipitation is more sensitive than that to temperature. The response of runoff to temperature is only one-third of the response to precipitation. A decrease in temperature may offset the impact of decreasing rainfall on runoff, while an increase in both rainfall and temperature leads to strongest runoff variations in the YRB.